If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-90x+45=45x-45
We move all terms to the left:
-90x+45-(45x-45)=0
We get rid of parentheses
-90x-45x+45+45=0
We add all the numbers together, and all the variables
-135x+90=0
We move all terms containing x to the left, all other terms to the right
-135x=-90
x=-90/-135
x=2/3
| 2x-2-7x=-2x-6-2x+10 | | 7x+6x=15/x | | 3b=2b+8 | | 3n-4=12 | | F(x)=x^2-5x+24 | | 5x-66=2x+50 | | -7(6x-9)=-42x+63 | | 1-6n=1+4n | | 6x-3-2x=4x | | 259=7(6x-3)2x | | 6(7-2x)=5x-21 | | 6(n-3)=8 | | Y=64x | | x-8=0,85x | | 2(u-4)-6=-3(-5u+6)-3u | | 183=-8a+7(5a+4) | | 22-4x+6x=22 | | -12=11t-5t^2 | | -3a+9=6a+15 | | -3(7w-3)+6w=3(w+1) | | 102=6(1+2p) | | |x-8|=30 | | (3x+2)(x-6)=6 | | 2a=90 | | x/2=225 | | 8.n=5.8 | | (3x)+(2x+4)+(5x−8)=180 | | Y=1.7506x+5.2524 | | 2x+-2=17 | | 36=(6^(10x))*(6^(2x)) | | 11x^2-6x-140=0 | | 3x-5(x-3)=-6+3x-4 |